Correlation of eccentric strength, reactive strength, and leg stiffness with running economy in well-trained distance runners - Li, F.; Newton, R. U.; Shi, Y.; Sutton, D.; Ding, H. (The Journal of Strength and Conditioning Research, 2021)
Neuromuscular characteristics play a critical role in distance running performance; however, their relationship with running economy (RE) remains unclear. The purpose of this study was to evaluate the correlations between 1 repetition maximum (1RM) strength, eccentric strength, reactive strength, leg stiffness, and RE at 12-16 km·h-1 among well-trained male runners. Twenty-eight male collegiate distance runners participated in test sessions on 3 separate days. In the first session, their 1RM squat strength, countermovement jump (CMJ), and drop jump performances were measured. In the second session, the leg press (LP) eccentric and concentric peak force, and leg stiffness (Kleg) were evaluated. In the final session, 12, 14, and 16 km/h RE, blood lactate concentration, and maximum oxygen uptake were measured. There were significant relationships between the LP eccentric peak force, eccentric:concentric peak force ratios (Efl:Cex), RE at speeds of 12, 14, and 16 km/h (r = -0.527 to -0.630; p < 0.01), reactive strength index (r = -0.419 to -0.572; p < 0.05), and Kleg (r = -0.686 to -0.761; p < 0.001) were significantly correlated with RE at 12, 14, and 16 km/h. No significant association was found between LP concentric peak force, 1RM squat strength, CMJ, and RE at any speed (p > 0.05). Superior RE among distance runners may be related to greater eccentric strength, elastic energy utilization, and stiffer lower limbs during running but not to maximal muscle strength per se. Coaches should focus on these neuromuscular characteristics to improve running performance.